Insights into the bacterial and fungal communities and microbiome that causes a microbe outbreak on ancient wall paintings in the Maijishan Grottoes. (September 2021) - He, Dongpeng; Wu, Fasi; Ma, Wenxia; Zhang, Yong; Gu, Ji-Dong; Duan, Yulong; Xu, Ruihong; Feng, Huyuan; Wang, Wanfu; Li, Shi-Weng
Abstract: The Maijishan Grottoes, located on the ancient Silk Road in West China, was constructed from the 4th centuries onward for more than 1500 years and became a UNESCO World Cultural Heritage in 2014. A severe microbe outbreak occurred on the wall paintings in the caves of the Maijishan Grottoes in 2018. To prevent and control microbial damage to the wall paintings, we analyzed the bacterial and fungal communities in the normal wall samples and those with microbial plaques using high-throughput sequencing and the environmental factors associated with the microbe outbreak. The results showed that the normal wall samples were dominated by bacterial phyla Actinobacteria (71.7%), Proteobacteria (17.8%), Firmicutes (6.5%), Chloroflexi (2.4%), and Bacteroidetes (0.9%), and fungal families Trichocomaceae (43.4%), unclassified Capnodiales (23.2%), unclassified Ascomycota (12.1%), Teratosphaeriaceae (10.2%), and unclassified Eurotiomycetes (6.2%). The wall samples with microbial plaques were dominated by bacterial Actinobacteria (92.9%), Proteobacteria (5.3%), Firmicutes (1.1%), and Chloroflexi (0.3%) and fungal families unclassified Eurotiomycetes (93.3%), unclassified Ascomycota (3.3%), and Microascaceae (2.9%). These results indicated the great changes in bacterial and fungal communities during the microbe outbreak. The dominant fungus in the wall samples with microbial plaques was isolated and identified as a potential novel species which has 92% ITS sequence similarity with Arachnomyces sp. Canonical correspondence analysis (CCA) revealed that the microbe outbreak was primarily attributed to the excessive air humidity inside and outside of the caves. Thus, air humidity management is important for protecting the ancient wall paintings from microbial colonization and attack. Highlights: Bacterial and fungal community structures in ancient wall paintings of the Maijishan Grottoes were evaluated. Bacterial and fungal community structures displayed dissimilarity among the caves. Microtome that causes a microbial outbreak on the wall paintings was analyzed and isolated. The isolated dominant fungus associated with the microbial outbreak on the wall paintings is a potential novel species. Excessive humidity was the kay environmental factor that triggered the microbial breakout event.